Effect of fencing on regional ecological networks in the northern Tibetan Plateau - Zhao, Yifei; Liu, Shiliang; Dong, Yuhong; Wang, Fangfang; Liu, Hua; Liu, Yixuan (Frontiers in Plant Science, 2023)
Fencing is an essential measure for the rehabilitation and conservation of grasslands on the Qinghai-Tibet Plateau. However, its construction could change the distribution and migration of wildlife, thus affecting the integrity of the ecological networks for local wild animal movement. It is of great significance to quantify the potential impact of fencing on ecological network connectivity associated with land-use changes at regional scale. In this study, taking the northern Tibetan Plateau as the study area, we explored the ecological network change using circuit theory approach under different scenarios at county scale. Among them, this study set up four different scenarios according to the economic growth rate, population growth rate and the sustainable development of society and environment. The results showed that: 1) with increased grazing intensity and enhanced human activities from 1990 to 2015, the grasslands of the northern Tibetan Plateau were greatly degraded, most of which was converted into the barren land, and the conversion proportion was as high as 90.84%, which lead to a decreasing trend of the current density of ecological network in most counties and deterioration of ecological connectivity; 2) fencing construction has reduced regional current density, while fencing intensity is positively correlated with current density loss at county scale. Among them, the counties with serious current density loss were distributed in the northwest and southeast regions. The maximum loss ratio is 39.23%; 3) under four different future land use scenarios, coordinated economic, social and environmental development will have a positive effect on the ecological network.